PENGARUH STRATEGI PEMBELAJARAN PBL DAN GAYA BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 4 SDN 02 CUPAK TANGAH KECAMATAN PAUH KOTA PADANG - Mira Sasmita; Efendi Napitupulu; Teguh Prakoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to analyze the effects of Problem-Based Learning (PBL) strategy and learning styles on Indonesian language learning outcomes of 4th grade students at SDN 02 Cupak Tangah,Pauh District, Padang City. The research employed a quantitative experimental approach with a 2×2 factorial design, involving 54 students divided into two groups: an experimental group using PBL strategy (28 students) and a control group using conventional strategy (26 students). Based onlearning styles, there were 33 students with visual learning style and 21 students with auditory learning style. The research instruments consisted of Indonesian language learning achievement tests andlearning style questionnaires. Data were analyzed using two-way ANOVA with significance level α =0.05. The research findings indicated that: (1) there was a highly significant effect of PBL learning strategy on Indonesian language learning outcomes (F = 121.371, p < 0.001), with the PBL group mean score (93.46) being 7.73 points higher than the conventional group (85.81); (2) there was no significant effect of learning styles on Indonesian language learning outcomes (F = 0.541, p = 0.466),with the mean difference between visual (89.55) and auditory (90.14) learning styles being only 0.59points; (3) there was no significant interaction between PBL learning strategy and learning styles on Indonesian language learning outcomes (F = 0.272, p = 0.604). Prerequisite tests showed that the datawere normally distributed (Kolmogorov-Smirnov p = 0.200) and had homogeneous variance (Levene's test p = 0.110).